3D-Printed Mesoporous Carrier System for Delivery of Poorly Soluble Drugs - Christos S. Katsiotis; Michelle Åhlén; Maria Strømme; Ken Welch (MDPI AG, 2021)
Fused deposition modelling (FDM) is the most extensively employed 3D-printing technique used in pharmaceutical applications, and offers fast and facile formulation development of personalized dosage forms. In the present study, mesoporous materials were incorporated into a thermoplastic filament produced via hot-melt extrusion and used to produce oral dosage forms via FDM. Mesoporous materials are known to be highly effective for the amorphization and stabilization of poorly soluble drugs, and were therefore studied in order to determine their ability to enhance the drug-release properties in 3D-printed tablets. Celecoxib was selected as the model poorly soluble drug, and was loaded into mesoporous silica (MCM-41) or mesoporous magnesium carbonate. In vitro drug release tests showed that the printed tablets produced up to 3.6 and 1.5 times higher drug concentrations, and up to 4.4 and 1.9 times higher release percentages, compared to the crystalline drug or the corresponding plain drug-loaded mesoporous materials, respectively. This novel approach utilizing drug-loaded mesoporous materials in a printed tablet via FDM shows great promise in achieving personalized oral dosage forms for poorly soluble drugs.